Blockchain: finding real benefits beyond the hype - Addison, Chris; Lohento, Ken (Technical Centre for Agricultural and Rural Cooperation, 2018)
One technology apparently has the potential to provide answers to a number of issues in agriculture, from farmer IDs to smart contracts and traceability… It is the blockchain.